RELATING THE QCD POMERON TO AN EFFECTIVE GLUON MASS - Halzen, F.; Krein, G.; Natale, A. A. (American Physical Soc, 1993)
We construct the Pomeron as an exchange of two nonperturbative gluons, where the nonperturbative gluon propagator is described by an approximate solution of the Schwinger-Dyson equation which contains a dynamically generated gluon mass. We compute the total and elastic differential (dsigma/dt) cross sections for pp scattering, obtaining agreement with the experimental data for a gluon mass m = 370 MeV for LAMBDA(QCD) = 300 MeV. In particular, the Pomeron effectively behaves like a photon-exchange diagram with a coupling determined by the glucon mass.